Etiology, Seasonality, and Clinical Features of Viral Respiratory Tract Infections in Children Hospitalized With Acute Bronchiolitis: A Single-Center Study - Şule Gökçe MD; Zafer Kurugöl PhD; Güldane Koturoğlu PhD; Candan Çiçek PhD; Aslı Aslan MD (SAGE Publishing, 2017)
The purpose of this study was to evaluate the viral frequency, seasonality, and clinical and demographic features of patients hospitalized with acute bronchiolitis. A cross-sectional, descriptive study was performed in 316 infants younger than 2 years of age who were hospitalized for acute viral bronchiolitis. Respiratory tract infection agents were investigated with polymerase chain reaction (PCR). A total of 316 infants were included in this study. Of the 316 infants, at least one respiratory tract pathogen was detected in 75% (237/316). Respiratory syncytial virus (RSV) was the most common virus identified in 127 infants (40.1%) followed by rhinovirus (n = 78, 24.6%). In this study, where viral agents were determined via PCR in patients who were followed-up due to the diagnosis of acute bronchiolitis, RSV was detected as the most common agent, as in other studies. In almost half of the RSV-positive patients, RSV was accompanied by a second or third agent.